Ülkemizde sağlık hizmetlerinde profesyonelleşme kapsamında hemşireliğin değerlendirilmesi ve Avrupa Birliği’ne uyum süreci - Özlük, Bilgen (My University, 2006)
1. ÖZET Bu çalışma; Avrupa Birliği (AB)’ne uyum süreci içerisinde olan Türkiye’de sağlık hizmetleri içinde hemşireliğin profesyonelleşmesi sürecinde değerlendirilmesi amacıyla kalitatif olarak yapılmıştır. Araştırma kapsamına, Türkiye’de hemşirelik alanında öncülük etmiş, profesyonelleşmeye katkıda bulunmuş ve Avrupa Birliği konusunda uzman kişiler arasından 15 kişi alınmıştır. Çalışmaya katılan kişilere, hazırlanmış olan sorular doğrultusunda yarı yapılandırılmış derinlemesine yüz yüze görüşme metodu uygulanmıştır. Elde edilen bulguların değerlendirilmesinde, görüşme kayıtlarının deşifresi ve görüşmecilerin görüşleri araştırmacının yaptığı analizle yorumlanmıştır. Çalışma sonucunda, Türkiye’de hemşirelik mesleğinin, profesyonellik kriterlerine göre ve toplum tarafından hala profesyonel bir meslek olarak kabul edilmediği tespit edilmiştir. Farklı düzeydeki hemşirelik eğitiminin hemşireliğin toplum içinde meslek olarak tanınmasına engel olduğunu, hemşirelik mesleği ile ilgili bir alt yapı sağlanamadığı görülmüştür. Hemşirelik mesleği ile ilgili yasanın, hemşirelik mesleğinin profesyonelleşmesini engelleyen nedenlerin başında geldiğini, başka bir mesleğe bağımlı kıldığını, güncelliğini kaybetmiş ve işleyişi güçleştiren bir yasa olduğu görülmüştür. Hemşirelik mesleğiyle ilgili aktif, yaptırım gücü olan bir örgütün olmayışı, hemşirelik mesleğinin profesyonelleşmesini olumsuz yönde etkilediği görülmüştür. Hemşirelik mesleğinin profesyonelleşmesi yönünde çalışmalar olduğunu, fakat çalışmaların yetersiz olduğu saptanmıştır. AB’ye uyum sürecinde; AB kriterlerinin yaptırımı olan, itici bir güç olarak hemşirelik mesleğinin gelişmesi ve profesyonelleşmesi adına olumlu olacağı görülmüştür. 2.

EVALUATION OF NURSING PROFESSION WITHIN THE SCOPE OFPROFESSIONALAZATION IN HEALTH SERVICES IN OUR COUNTRY AND THE PROCESS OF HARMONIZATION TO THE EUROPEAN UNION This study has been performed qualitatively for the purpose of evaluating the nursing in its process of getting professional within the health services in Turkey which is in process of harmonization with the European Union (EU). 15 persons that pioneered on the area of nursing in Turkey, contributed to the process of professionalism and that are specialized on the subject of the EU were taken into the coverage of the study. The persons that participated in the study are applied the in-depth face-to-face interview method which is semi-structured in accordance with the questions prepared. As a result of the evaluation of the results obtained, deciphering the interview records and opinions of the interviewers were interpreted by means of the analysis that was performed by the researcher. As a consequence of the aforementioned study, it was determined that the profession of nursing is not accepted as a professional occupation today by the community in Turkey, and according to the criteria of professionalism. It was also seen that the education of nursing at different levels prevented nursing to be accepted as a profession in community and no substructure could be provided relating to the profession of nursing. It is seen that the law concerning the profession of nursing is one of the most important reasons that prevent the profession of nursing to be professional and made it bound to another profession, and it is a law which needs to be updated and which makes operation difficult. It was seen that the lack of an organization which has an active sanction power relating to the profession of nursing affected the getting professional of the profession of nursing negatively. There are some works for getting professional of the profession of nursing; however, the works remain insufficient. In the process of harmonization with the EU, it was seen that criteria of the EU will be affirmative for getting professional of the profession of nursing and for its development as a pushing power with the necessary sanctions. Nursing, Profession, Professionalism, European Union.
Keywords: Avrupa Birliği_Sağlık Hizmetleri; Hemşirelik_Sağlık Hizmetleri_Türkiye